Konstruksi Kearifan Lokal Islam Aboge di Probolinggo - Haqqul Yaqin (HUMANISTIKA : Jurnal Keislaman, 2018)
Religion is a phenomenon associated with many dimensions, including the social dimension. Social thinkers such as Durkheim, Marx, and Weber also imply that religion is essentially more of a social aspect than a purely individual thing. Hence it can be said that there is an inevitable connection between religion as one of the social phenomena with many aspects of community life. Religion can also be said to be inseparable from the influence of the context of the society in which the religion develops. These influences can then be carried away in tradition and it is not uncommon to find that the content of religious interpretation has already contained a tendency of certain political interests.